Preschool teachers’ perceptions of cultural competencies on multicultural education - Yaşar Ekici, Fatma; Ekici, Fatma Yaşar (Afro-Eurasian Research, 2017)
The aim of this study is to examine preschool teachers’ perceptions of cultural competencies on multicultural education. Survey method was used. The study group consists of a 150 preschool teachers working in 22 preschool education institutions in 4 districts (Bahçelievler, Küçükçekmece, Sultangazi, Güngören) of Istanbul in 2015-2016 academic year. The measurement tool used for the data collection were the “Personal Information Form” and the “Multicultural Education Cultural Competency Scale " developed by Acar-Çiftçi (2015). In the analysis of the data, SPSS 20 package program was applied. At the end of the research it is found that preschool teachers’ perceptions of cultural competencies on multicultural education do not significantly vary by school type they work in, age, athnic origin, education level, Professional senirity and the geographical region where they reside in. Different from that; Preschool teachers’ perceptions of cultural competencies on multicultural education significantly vary by the state of getting education on multicultural education.
* Fatma Yaşar Ekici. İstanbul Sabahattin Zaim Üniversitesi, Eğitim Fakültesi, İstanbul, Türkiye.
Keywords: Preschool; Multicultural education; Cultural competency